(untitled) (Bangladesh Journal of Neuroscience, 2019)
Background: AD is the most common cause of dementia in elderly which causes economic burden for the affected individual, caregivers and society. The objective of this study was to see demographic characteristics among AD patients and it will provide magnitude of the problem and planning of health programme for prevention of disease. Methods: This observational analytical study was carried out in the Neurology ward, OPD and Dementia clinic of BSMMU, Dhaka from May’ 15 to February’ 17. A total of 45 patients were recruited as study population after satisfying all the criteria for enrollment. Results: A total of 27 male and 18 female with mean age of 69.20 ± 11.16 years, constituted as cases. Conclusion: The occurrence of AD found more after the age of 65 years. The present study found that lower educational level is associated with more chance of getting AD. Higher rate of Alzheimer’s disease was found in older man than women. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 10-13